Predictors of mortality in acute lung injury during the era of lung protective ventilation. Issue 11 (19th June 2008) - Seeley, E; McAuley, D F; Eisner, M; Miletin, M; Matthay, M A; Kallet, R H
Abstract : Background: Lung protective ventilation has been widely adopted for the management of acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). Consequently, ventilator associated lung injury and mortality have decreased. It is not known if this ventilation strategy changes the prognostic value of previously identified demographic and pulmonary predictors of mortality, such as respiratory compliance and the arterial oxygen tension to inspired oxygen fraction ratio (Pao 2 /Fio 2 ). Methods: Demographic, clinical, laboratory and pulmonary variables were recorded in 149 patients with ALI/ARDS. Significant predictors of mortality were identified in bivariate analysis and these were entered into multivariate analysis to identify independent predictors of mortality. Results: Hospital mortality was 41%. In the bivariate analysis, 17 variables were significantly correlated with mortality, including age, APACHE II score and the presence of cirrhosis. Pulmonary parameters associated with death included Pao 2 /Fio 2 and oxygenation index ((mean airway pressure×Fio 2 ×100)÷Pao 2 ). In unadjusted analysis, the odds ratio (OR) of death for Pao 2 /Fio 2 was 1.57 (CI 1.12 to 3.04) per standard deviation decrease. However, in adjusted analysis, Pao 2 /Fio 2 was not a statistically significant predictor of death, with an OR of 1.29 (CI 0.82 to 2.02). In contrast, oxygenation index (OI) was a statistically significant predictor of death in both unadjusted analysis (OR 1.89 (CI 1.28 to 2.78)) and in adjusted analysis (OR 1.84 (CI 1.13 to 2.99)). Conclusions: In this cohort of patients with ALI/ARDS, OI was an independent predictor of mortality, whereas Pao 2 /Fio 2 was not. OI may be a superior predictor because it integrates both airway pressure and oxygenation into a single variable.